STRATEGI PENATAAN KAWASAN PETERNAKAN DI KABUPATEN BLITAR - Ginting, Eliezer (Jurnal Penyuluhan, 2006)
The research result shows that the zoning of KINAK is based on the critical and even less productive field for planting. Furthermore, several factors have significant effect on KINAK arrangement social norm system of the local society as well as general and specific layout plant of Blitar regency. The effort of matching KINAK with the availability of potential circumstance and transportation bring about advantages to marketing crops and climate. There has been no change in location enterprise policy. There were two types of work patterns in terms of social-economy such as horizontal and vertical. Horizontally, the work pattern was created among farmers. Vertically the work pattern was built in such a way that farmers have relation to some local poultry shop and Extension Service who are regarded as technical assistant. In addition to it consequence, the arrangement of KINAK has both increased the number of farmer and poultries being raised, and exceded social stratification that is regarded as social honor by people around KINAK.